5(v-2)-6=2(-8v+7)-3v

Simple and best practice solution for 5(v-2)-6=2(-8v+7)-3v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(v-2)-6=2(-8v+7)-3v equation:


Simplifying
5(v + -2) + -6 = 2(-8v + 7) + -3v

Reorder the terms:
5(-2 + v) + -6 = 2(-8v + 7) + -3v
(-2 * 5 + v * 5) + -6 = 2(-8v + 7) + -3v
(-10 + 5v) + -6 = 2(-8v + 7) + -3v

Reorder the terms:
-10 + -6 + 5v = 2(-8v + 7) + -3v

Combine like terms: -10 + -6 = -16
-16 + 5v = 2(-8v + 7) + -3v

Reorder the terms:
-16 + 5v = 2(7 + -8v) + -3v
-16 + 5v = (7 * 2 + -8v * 2) + -3v
-16 + 5v = (14 + -16v) + -3v

Combine like terms: -16v + -3v = -19v
-16 + 5v = 14 + -19v

Solving
-16 + 5v = 14 + -19v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '19v' to each side of the equation.
-16 + 5v + 19v = 14 + -19v + 19v

Combine like terms: 5v + 19v = 24v
-16 + 24v = 14 + -19v + 19v

Combine like terms: -19v + 19v = 0
-16 + 24v = 14 + 0
-16 + 24v = 14

Add '16' to each side of the equation.
-16 + 16 + 24v = 14 + 16

Combine like terms: -16 + 16 = 0
0 + 24v = 14 + 16
24v = 14 + 16

Combine like terms: 14 + 16 = 30
24v = 30

Divide each side by '24'.
v = 1.25

Simplifying
v = 1.25

See similar equations:

| (x-3/5+x)=10/14 | | -42.84b+8=5 | | 4x+5y=7fory | | 32t^4-162y^4=0 | | 2z-4=10 | | 3f+2+9=13+5f | | 10(6+2x)=-2(8x+6) | | (-4x^2)+(5y)-(-6x^2)-(7y)=x | | Hg(x)=3.08(138)sqrt+18.97 | | 9+-4=x | | f(-3)=3(-3)-15 | | ln(x^2+7x-31)=0 | | 6x^2-16x-360=0 | | 9(y+9)=6+8y | | 10x-5=0 | | 15-n=n+5 | | 2(p-1)=7p+3-4p | | 15-n=5+n | | 5X+2=3X-(8x+2) | | -6+(-4)=x | | 15+n=5+n | | 10+n=n+5 | | 3r+3=6r-1 | | -3+8h=-5 | | -0.002x^2+0.5x-10=0 | | 7p-14=3(p-8)-6(3-3p) | | 3x+2=2-3x | | 6d+7=39 | | 9/7= | | X^3-100x^2-1250=0 | | 45*n=400 | | 4(z-2)=2(z+3) |

Equations solver categories